Is liver transplantation 'out-of-hours' non-inferior to 'in-hours' transplantation? A retrospective analysis of the UK Transplant Registry. Issue 2 (20th February 2019) - Halliday, Neil; Martin, Kate; Collett, David; Allen, Elisa; Thorburn, Douglas
Abstract : Objectives: Increased morbidity and mortality have been associated with weekend and night-time clinical activity. We sought to compare the outcomes of liver transplantation (LT) between weekdays and weekends or night-time and day-time to determine if 'out-of-hours' LT has acceptable results compared with 'in-hours'. Design, setting and participants: We conducted a retrospective analysis of patient outcomes for all 8816 adult, liver-only transplants (2000–2014) from the UK Transplant Registry. Outcome measures: Outcome measures were graft failure (loss of the graft with or without death) and transplant failure (either graft failure or death with a functioning graft) at 30 days, 1 year and 3 years post-transplantation. The association of these outcomes with weekend versus weekday and day versus night transplantation were explored, following the construction of a risk-adjusted Cox regression model. Results: Similar patient and donor characteristics were observed between weekend and weekday transplantation. Unadjusted graft failure estimates were 5.7% at 30 days, 10.4% at 1 year and 14.6% at 3 years; transplant failure estimates were 7.9%, 15.3% and 21.3% respectively. A risk-adjusted Cox regression model demonstrated a significantly lower adjusted HR (95% CI) of transplant failure for weekend transplant of 0.77 (0.66 to 0.91) within 30 days, 0.86 (0.77 to 0.97) within 1 year, 0.89 (0.81 to 0.99) within 3 years and for graft failure of 0.81 (0.67 to 0.97) within 30 days. For patients without transplant failure within 30 days, there was no weekend effect on transplant failure. Neither night-time procurement nor transplantation were associated with an increased hazard of transplant or graft failure. Conclusions: Weekend and night-time LT outcomes were non-inferior to weekday or day-time transplantation, and we observed a possible small beneficial effect of weekend transplantation. The structure of LT services in the UK delivers acceptable outcomes 'out-of-hours' and may offer wider lessons for weekend working structures.